The impact of Work School Conflict and Work School Enrichment on job satisfaction and academic satisfaction - Jacobs, Carla Colleen (2019)
More students are combining their higher education with paid work necessitated by the increasing cost of living and the costs of tertiary education. Simultaneously, higher education in South Africa (SA) is plagued with low success rates (Department of Higher Education and Training, 2017). The increase in combining work and study could be a compounding factor toward these low success rates. The constructs Work School Conflict (WSC) and Work School Enrichment (WSE), have been used to explore the impact of working while studying. The current study builds on this research in the SA context. Working students responded to self-report survey (N = 379). Regression analysis revealed WSC to have a negative relationship with both job satisfaction and academic satisfaction and WSE to have a positive relationship with job satisfaction and academic satisfaction. Social support from supervisors was found to buffer the negative relationship WSC has with academic satisfaction. However, no evidence was found for the other moderation hypotheses. The findings from this study support previous research regarding the positive and negative impacts holding a work and school role simultaneously can have in the school and work domains. Further theoretical and practical implications of these findings are discussed.